2003
DOI: 10.1111/1469-7610.00179
|View full text |Cite
|
Sign up to set email alerts
|

A twin study of anxiety‐related behaviours in pre‐school children

Abstract: These data provide evidence for phenotypic and genetic overlap as well as differentiation between aspects of anxiety-related behaviours in young children. We conclude that research with young children will benefit from more specific assessments of anxiety-related behaviours in addition to less differentiated assessments of 'internalising' symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
221
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(247 citation statements)
references
References 82 publications
25
221
0
1
Order By: Relevance
“…Specifically, for aggression and withdrawn behaviors, genetic influences were stronger for girls and shared environmental influences were stronger for boys (Derks et al, 2004), whereas the reverse was true for overall externalizing problems on the CBCL broadband Externalizing scale (Bartels et al, 2004). van der Valk et al, 2001), in the TEDS sample, anxiety-related behaviors displayed significant and substantial shared environmental influences (Eley et al, 2003). These findings highlight the need to consider the extent to which empirical results converge across different measures.…”
Section: Nih Public Accessmentioning
confidence: 88%
“…Specifically, for aggression and withdrawn behaviors, genetic influences were stronger for girls and shared environmental influences were stronger for boys (Derks et al, 2004), whereas the reverse was true for overall externalizing problems on the CBCL broadband Externalizing scale (Bartels et al, 2004). van der Valk et al, 2001), in the TEDS sample, anxiety-related behaviors displayed significant and substantial shared environmental influences (Eley et al, 2003). These findings highlight the need to consider the extent to which empirical results converge across different measures.…”
Section: Nih Public Accessmentioning
confidence: 88%
“…This fear typically diminishes dramatically during early childhood (Muris, Meesters, Merckelbach, Sermon, & Zwakhalen, 1998), an age when fear-based anxiety disorders, such as separation anxiety disorder, social phobia, and specific phobias, are likely to onset (Kessler et al, 2005). Fear in these young children has significant genetic overlap with shyness/inhibition (62%) and negative mood (53%; Eley et al, 2003), suggesting developmental continuity with later internalizing disorders that share these traits, particularly disorders in the FA subfactor. These disorders are characterized by behavioral constraint (Krueger, 1999a) and intense physiological hyperarousal (PH), such as heart racing, sweating, and shortness of breath particularly in response to stressors (Cuthbert et al, 2003;Hofmann, Moscovitch, & Kim, 2006;Martin-Soelch, Stocklin, Dammann, Opwis, & Seifritz, 2006).…”
Section: Physiological Hyperarousal Liabilitymentioning
confidence: 99%
“…For example, events that involve exposure to dangerous circumstances, such as exposure to violent acts, typically produce characteristic signs of fear in a child, whereas events that involve exposure to loss of vital relationships, such as decreased contact with a loved one, typically produce characteristic signs of dysphoria (Eley and Stevenson, 2000). Such distinctions between fear-and griefrelated reactions can be made relatively reliably, even among preschool children (Eley et al, 2003). In this area of research, events involving fear have been shown to exhibit close links to anxiety disorders, whereas events involving loss have been shown to exhibit close links to mood disorders (Eley and Stevenson, 2000;Kendler et al, 2003).…”
Section: Stress Trauma and Psychopathology In Children And Adolescentsmentioning
confidence: 99%